Unified enterprise modelling language-based interoperability for collaborative access control framework in critical infrastructures. (7th February 2020) - Baina, Amine; Benali, Khalid; Bellafkih, Mostafa; Aali, Nawal Ait
Due to physical and logical vulnerabilities, a critical infrastructure (CI) can encounter failures of various degrees of severity, and since there are many interdependencies between CIs, simple failures can have dramatic consequences on the whole infrastructure. In this paper, we mainly focus on malicious threats that might affect the communication and information systems (the critical information infrastructure, or CII) dedicated to critical infrastructures. We define a new collaborative access control framework called PolyOrBAC, to address the security problems that are specific of CIIs. This approach offers each organisation taking part in the CII the capacity of collaborating with the other ones, while maintaining a control on its resources and on its internal security policy. The approach is demonstrated on a practical scenario, based on real emergency actions in an electric power grid infrastructure.